Sintesis dimensi dan analisis kinematik mekanisme empat batang dengan rantai kinematik RSSR - Rahim Isnan Al Hilman; Syamsul Huda; Mulyadi Bur (Badan Kerja Sama Teknik Mesin Indonesia, 2016)
Spatial four bar linkage mechanism can be applied to transmit rotation from crank to coupler with various orientation of axis rotation. Revolute-spherical-spherical-revolute (RSSR) one of popular configuration of spatial four bar linkage mechanism. The mechanism was compossed of four kinematic constants that shoud be determined to yield specified relationship between input and output displacements. In this paper was carried out the dimensional synthesis of the RSSR mechanism using function generation method with consideration of limitation of spherical joint workingspace and transmision angle. For case study was syntesized the RSSR four bar mechanism where orientation of crank axis rotation is perpendicular to follower axis rotation and the two axes lie on the same plane. The crank was desired to rotate fully cycle and the follower rotate with the span 1800 (0 â‰¤ ï¦ â‰¤ 180o) . It was obtained the otimal dimension of crank, coupler and folower, 5.55, 8.07 and 2.79 units respectivelly. The displacement analysis was applied to evalute performance of the mechanism. The obtained mechanism can perform fully cycle crank rotation and 133.20 span motion of follower and tranmission angle between coupler and follower varies between 38.4o and 101.6o.